Synthesis of (Triphenylphosphoranylidene)spiro[cyclopentene-1,3′-indole]s by a Three-Component Reaction of Triphenylphosphine, Dialkyl Acetylenedicarboxylates, and 3-(Aroylmethylene)-1,3-dihydro-2H-indol-2-ones - Gong, Hui; Sun, Jing; Yan, Chao-Guo (Synthesis, 2014)
The three-component reaction of triphenylphosphine, a dialkyl acetylenedicarboxylate, and a 3-(aroylmethylene)-1,3-dihydro-2H-indol-2-one in 1,2-dimethoxyethane at room temperature gave the corresponding functionalized (triphenylphosphoranylidene)spiro[cyclopentene-1,3′-indole]s in satisfactory yields.
Keywords: spiro compounds; heterocycles; phosphorus; indoles; alkynes; multicomponent reactions